2007
DOI: 10.1159/000099652
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler Velocity Is Not Totally Preload-Independent: A Study in a Uremic Population after Hemodialysis

Abstract: Objectives: The aim of this study was to investigate the changes of regional tissue Doppler velocity after volume removal following regular hemodialysis (HD) in uremic patients. Is tissue Doppler velocity really preload-independent? Background: Diastolic dysfunction was divided into four stages: normal pattern, abnormal relaxation pattern, pseudonormalization pattern, and restrictive pattern. Pulse wave Doppler and color Doppler echocardiography were important diagnostic tools for these forms of diastolic dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
3
8
0
1
Order By: Relevance
“…Thus the situation after food intake does not correspond from a hemodynamic point of view to other situations where loading conditions have been altered. The impact of changes in loading conditions on pulsed Doppler and tissue Doppler variables has been investigated in several different ways such as after tilt‐test, hemodialysis, active change of posture, nitroglycerine application, leg lifting 31–37 . Our findings that mitral and pulmonary venous flow changed after a meal are in concordance with several previous investigations that have used other methods of changing loading conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Thus the situation after food intake does not correspond from a hemodynamic point of view to other situations where loading conditions have been altered. The impact of changes in loading conditions on pulsed Doppler and tissue Doppler variables has been investigated in several different ways such as after tilt‐test, hemodialysis, active change of posture, nitroglycerine application, leg lifting 31–37 . Our findings that mitral and pulmonary venous flow changed after a meal are in concordance with several previous investigations that have used other methods of changing loading conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, PW over the mitral valve or in the pulmonary vein is more prone to be affected than TDI. The impact of changes in loading conditions on PW and TDI variables has been investigated in several different ways such as after tilt‐test, haemodialysis, active change of posture, nitro‐glycerine application, leg lifting or food intake (Stoddard et al ., ; Downes et al ., ; Voutilainen, ; Møller et al ., ; Barberato et al ., ; Baldi et al ., ; Lee et al ., ; Dencker et al ., ). Most of these changes in loading conditions are irrelevant in clinical practice and to the data in this summary, because you usually know the subjects′ posture or at which elevation they have their legs.…”
Section: Discussionmentioning
confidence: 99%
“…Weighted mean for reported values from selected studies c 20-29 years 30-39 years 40-49 years 50-59 years 60-69 years 70-79 years 80-89 years e' sept (cm s À1 ) (n = 3035) (Munagala et al, 2003;Park et al, 2007;Daimon et al, 2008;Innelli et al, 2008;Okura et al, 2009;Boyd et al, 2011). been investigated in several different ways such as after tilttest, haemodialysis, active change of posture, nitro-glycerine application, leg lifting or food intake (Stoddard et al, 1989;Downes et al, 1990;Voutilainen, 1994;Møller et al, 1999;Barberato et al, 2004;Baldi et al, 2007;Lee et al, 2007;Dencker et al, 2011). Most of these changes in loading conditions are irrelevant in clinical practice and to the data in this summary, because you usually know the subjects 0 posture or at which elevation they have their legs.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in adults have shown that, in contrast to standard pulsed Doppler indices of left ventricular filling and Color M-mode flow propagation velocity, diastolic velocities of the mitral annulus assessed by DTI are relatively independent of preload [3]. Other studies have revealed contradictory results [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%